The Story in Primary Instruction: Sixteen Stories and How to Use Them - Allison, Samuel B. (Samuel Buell), 1861-1932; Perdue, H. Avis (Hannah Avis), 1858- (Salt Lake City, UT : Project Gutenberg, 2017)
"The Story in Primary Instruction: Sixteen Stories and How to Use Them" by Samuel B. Allison and H. Avis Perdue is a pedagogical guide written in the early 20th century. This instructional text aims to emphasize the importance of story content in primary education, asserting that engaging narratives can enhance children's language development and ethical understanding. Through the integration of folklore and tales tailored to young learners, the authors propose effective methods for teaching vocabulary, comprehension, and moral lessons within a structured educational framework. At the start of the book, the authors introduce their mission to reshape primary instruction by prioritizing substantive content over solely formal language skills. They critique traditional methods that focus excessively on mastering written forms, arguing instead for programs that resonate with children$1 (Bs natural interests and imaginative capacities. The opening chapters walk through practical approaches to selecting appropriate stories, fostering ethical reasoning in children, and correlating narratives with various educational activities, all designed to create a more enriching and purposeful learning environment. (This is an automatically generated summary.)s
Release date is 2017-02-05
E-text prepared by Cindy Horton, MFR, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Teaching